Pengaruh Kepuasan Kerja dan Komitmen Organisasi terhadap Organizational Citizenship Behavior di BPRS Harum Hikmahnugraha Garut - Maryani, Rani (Ma'soem University, 2025)
Based on the result of observations and interviews, the background to this research is the decline in the number of employess in recent years. This research aims to determine the influence of job satisfaction and organizational commitment, both partially and simultaneously, on organizational citizenship behavior at BPRS Harum Hikmahnugraha Garut. The object of research in this thesis is employess at BPRS Harum Hikmahnugraha Garut. The type of research is associative quantitative with primary data types. Data collection techniques include observation, interviews, literature studies and questionnaires. The population is 41 employees and the sample is 38 employees. The results of the research show that there is a significant influence between job satisfaction on organizational citizenship behavior, with test results where the calculated –t value < -t table (-2,130 < -2,028). There is a significant influence beetwen organizational commitment on organizational citizenship behavior, and the results t test where t value > t table (7,401 > 2,028). Simultaneously there is a significant influence between job satisfaction and organizational commitment on organizational citizenship behavior at BPRS Harum Hikmahnugraha Garut with the result of the F test where the calculated T value > F table (47,827 > 3,27).